Development, Validation and Inspection of the Applicability Domain of QSPR Models for Physicochemical Properties of Polybrominated Diphenyl Ethers - Papa, Ester; Kovarich, Simona; Gramatica, Paola (QSAR & combinatorial science, 2009)
Polybrominated diphenyl ethers (PBDEs) are a group of brominated flame retardants (BFRs), which were widely used in a variety of consumer products. Because of evidences of toxicity effects on different organisms and humans, as well as the ubiquitary profile of these compounds, PBDEs are considered an emerging group of toxic and persistent organic pollutants. However, due to the small amount of experimental data available, still little is known about the properties of most of these chemicals. In this study several physicochemical properties, experimentally available for few PBDE congeners and hexabromobenzene (HBB), were investigated through a modelling approach based on quantitative structure–property relationships (QSPR). The OLS regression models, based on theoretical molecular descriptors, are calculated for Henry's law constant, melting point, subcooled liquid vapor pressure, water solubility, octanol‐air partition coefficient, and octanol‐water partition coefficient. These models can be useful to predict the big amount of missing data and to plan safer alternatives to dangerous BFRs. The innovative aspect of the proposed models, compared to those already published in the literature, is their development according to the OECD principles for regulatory acceptability of QSARs. This includes the validation for predictivity (both by internal and external statistical validation) and the inspection of the applicability domain.